Public-private cooperation and agricultural development in Sub-Saharan Africa: a review of Nigerian growth enhancement scheme and e-voucher program - Emmanuel Olatunbosun Benjamin; Oreoluwa Ola; Hannes Lang; Gertrud Buchenrieder (Food Security, 2020)
The Growth Enhancement Scheme and e-voucher program, rolled out across Nigeria in 2011 by the federal government, provided the institutional basis for private agro-dealers to engage in the distribution of subsidized fertilizer, improved seeds and extension services to farmers. However, the impact of this policy on different modes of extension service delivery is still missing in literature. We apply an Ordinary Least Squared and Difference-in-Difference methodology on the (2010 and 2012) Living Standard Measurement Study of the World Bank. The results suggest that extension visitations as well as public extension services positively influence farm revenue. Furthermore, a substantial increase in fertilizer expenditure by farmers was observed, due to the e-voucher program, which could have contributed to the improved agricultural output witnessed in Nigeria post-Growth Enhancement Scheme era. Governments across Sub-Saharan Africa should implement policies that harness the economy of scale and scope of the private sector as well as information and communication technologies in delivering on time and adequate agricultural inputs to farmers.
Keywords: 630; Agricultural policy; Extension services; Fertilizer; Nigeria; Sub-Saharan Africa